Identification of the zebrafish maternal and paternal transcriptomes - Harvey, Steven A. (Company of Biologists, 2013)
Transcription is an essential component of basic cellular and developmental processes. However, early embryonic development occurs in the absence of transcription and instead relies upon maternal mRNAs and proteins deposited in the egg during oocyte maturation. Although the early zebrafish embryo is competent to transcribe exogenous DNA, factors present in the embryo maintain genomic DNA in a state that is incompatible with transcription. The cell cycles of the early embryo titrate out these factors, leading to zygotic transcription initiation, presumably in response to a change in genomic DNA chromatin structure to a state that supports transcription. To understand the molecular mechanisms controlling this maternal to zygotic transition, it is important to distinguish between the maternal and zygotic transcriptomes during this period. Here we use exome sequencing and RNA-seq to achieve such discrimination and in doing so have identified the first zygotic genes to be expressed in the embryo. Our work revealed different profiles of maternal mRNA post-transcriptional regulation prior to zygotic transcription initiation. Finally, we demonstrate that maternal mRNAs are required for different modes of zygotic transcription initiation, which is not simply dependent on the titration of factors that maintain genomic DNA in a transcriptionally incompetent state.